2022
DOI: 10.3389/fphar.2022.775798
|View full text |Cite
|
Sign up to set email alerts
|

Oral Astragalus Root Supplementation for Mild to Moderate Chronic Kidney Disease: A Self-Controlled Case-Series

Abstract: In this self-controlled case series, we aimed to investigate the variation in estimated glomerular filtration rate (eGFR) after taking astragalus-containing preparations in patients with mild to moderate chronic kidney disease (CKD) by retrospectively reviewing their charts in our clinic. We set the inclusion criteria as first-visit patients aged 20 years or older presenting to our clinic between 1 October 2014, and 31 June 2019, and who were prescribed astragalus-containing herbal preparations for any reason.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…CA is the top ingredient in Astragalus , which is one of the most widely used herbs in Chinese medicine to treat kidney disease[ 47 - 49 ]. The effectiveness of CA in CKD has been confirmed in recent years[ 50 - 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…CA is the top ingredient in Astragalus , which is one of the most widely used herbs in Chinese medicine to treat kidney disease[ 47 - 49 ]. The effectiveness of CA in CKD has been confirmed in recent years[ 50 - 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to small clinical trials, a systematic review of 66 studies involving 4,785 diabetic kidney disease participants also demonstrated the benefits of AR injection or preparation in reducing albuminuria, proteinuria, and serum creatinine levels ( Zhang L. et al, 2019 ). Furthermore, AR-containing preparations are effective in improving eGFR in patients with mild to moderate CKD ( Yoshino et al, 2022 ).…”
Section: Tcm For Treating Ckdmentioning
confidence: 99%
“…Astragalus root is a commonly used herb in traditional Chinese medicine. It has been reported to have renoprotective effects in some clinical and animal studies [ 5 , 6 ] and has been prescribed for patients with CKD in Japan and China [ 6 , 7 ] However, the pathophysiological mechanism has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%